Practice of skin protection and skin care among German surgeons and influence on the efficacy of surgical hand disinfection and surgical glove perforation - Harnoß, Julian-Camill; Brune, Laura; Ansorg, Jörg; Heidecke, Claus-Dieter; Assadian, Ojan; Kramer, Axel (BMC infectious diseases, 2014)
Surgical hand rub and healthy skin are basic requirements to prevent surgical site infections. Nevertheless, there is little knowledge about the current practice of skin protection and/or skin care products (SP/SC) using among surgeons as well as a lack of data pertaining to the influence of SP/SC on the antimicrobial efficacy of surgical hand rub.
Gesehen am 12.08.2020